Weighted Partial Radiation Efficiency and Effective Coverage as Key Performance Indicators for the Analysis of Automotive Antennas - Chaudhury, Nandan Dutta; Berkelmann, Lukas; Jannsen, Bert; Robert, Joerg (IEEE Conference on Antenna Measurements and Applications, CAMA, 2023)
It is essential to characterize the automotive antenna in its installed state because the metallic car body has a significant influence on the antenna's performance. In this connection, the 5GAA has recommended certain key performance indicators (KPIs), such as the Total Radiated Power (TRP), Partial Radiated Power (PRP), etc. for evaluating automotive antennas. However, these KPIs do not adequately reflect the vehicular integration effects on the antenna's performance. In order to fill this gap, two novel KPIs have been proposed in this paper, namely, the weighted Partial Radiation Efficiency and Effective Coverage. The weighting scheme for the calculation of the KPIs has been defined based on direction of importance. To demonstrate their significance, two different vehicular antenna integration topologies have been evaluated employing the KPIs. The results have been compared with existing metrics namely PRP and TRP.
CRIS-Team Scopus Importer:2024-11-19
Keywords: 5GAA; antenna placement; automotive antenna; autonomous vehicles; ITS; KPI; V2X